Sistem Pakar Diagnosa Penyakit Skistosomiasis Menggunakan Kombinasi Forward Chaining Dan Fuzzy Logic Takagi Sugeno Kang - Sarma Tampubolon (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
The purpose of this study was to determine the procedure for diagnosing Schistosomiasis at the Royal Maternity Hospital. The data collection technique used is the observation method. Schistosomiasis diagnosis expert system in this study was built using Visual Basic.Net 2008. The expert system method applied was Forward Chaining and Fuzzy Logic Takagi Sugeno Kang. From the results of the research conducted, it is known that Forward Chaining and Fuzzy Logic Takagi Sugeno Kang can provide diagnostic results that are relevant to the knowledge possessed by experts.